Contribution of Pseudomonas aeruginosa Exopolysaccharides Pel and Psl to Wound Infections - Fleming, Derek; Niese, Brandon; Redman, Whitni; Vanderpool, Emily; Gordon, Vernita; Rumbaugh, Kendra P. (Frontiers in Cellular and Infection Microbiology, 2022)
Biofilms are the cause of most chronic bacterial infections. Living within the biofilm matrix, which is made of extracellular substances, including polysaccharides, proteins, eDNA, lipids and other molecules, provides microorganisms protection from antimicrobials and the host immune response. Exopolysaccharides are major structural components of bacterial biofilms and are thought to be vital to numerous aspects of biofilm formation and persistence, including adherence to surfaces, coherence with other biofilm-associated cells, mechanical stability, protection against desiccation, binding of enzymes, and nutrient acquisition and storage, as well as protection against antimicrobials, host immune cells and molecules, and environmental stressors. However, the contribution of specific exopolysaccharide types to the pathogenesis of biofilm infection is not well understood. In this study we examined whether the absence of the two main exopolysaccharides produced by the biofilm former Pseudomonas aeruginosa would affect wound infection in a mouse model. Using P. aeruginosa mutants that do not produce the exopolysaccharides Pel and/or Psl we observed that the severity of wound infections was not grossly affected; both the bacterial load in the wounds and the wound closure rates were unchanged. However, the size and spatial distribution of biofilm aggregates in the wound tissue were significantly different when Pel and Psl were not produced, and the ability of the mutants to survive antibiotic treatment was also impaired. Taken together, our data suggest that while the production of Pel and Psl do not appear to affect P. aeruginosa pathogenesis in mouse wound infections, they may have an important implication for bacterial persistence in vivo.